If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3a + -2 + -2 = (3a + -2) Reorder the terms: -2 + -2 + 3a = (3a + -2) Combine like terms: -2 + -2 = -4 -4 + 3a = (3a + -2) Reorder the terms: -4 + 3a = (-2 + 3a) Remove parenthesis around (-2 + 3a) -4 + 3a = -2 + 3a Add '-3a' to each side of the equation. -4 + 3a + -3a = -2 + 3a + -3a Combine like terms: 3a + -3a = 0 -4 + 0 = -2 + 3a + -3a -4 = -2 + 3a + -3a Combine like terms: 3a + -3a = 0 -4 = -2 + 0 -4 = -2 Solving -4 = -2 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| -66=-3(6m+4) | | 3(x-1)=-2x+27 | | (d-8)(d-2)=0 | | 9(8c-9)=-35 | | 2x+18=-2 | | 3x+18=-2 | | 8+4=1440 | | 6.7(x-4)=-0.3x+15.2 | | 5d=4d-4 | | 6(x-4)+64=-2x | | -14I=56 | | (-2x+1)2=-5x-4 | | .5x^2=x-.5 | | 5(5c+3)=4(c+5) | | 2(x-4)=5x+17 | | 8d=7d-11 | | (c-3)-2c-(1-3c)=2 | | (x-3)(3x+4)=5(x+1)+8 | | 7y+y=8y+9 | | -6(4+6v)=120 | | 5(x+0)=-20 | | 7(9-6I)=-63 | | -7=x-3 | | 5(x+9)=-20 | | 9+12x=30+x | | -68=2(5n-4) | | -42=-8-6c | | 10=-8(2y-10) | | 7x(5x)= | | -7.6x=38.0 | | 8y-3=6y+37 | | -3(x+7)=-42 |